Zirconia bond strength durability following artificial aging: A systematic review and meta-analysis of in vitro studies - Athanasios E. Rigos; Katia Sarafidou; Eleana Kontonasaki (Elsevier, 2023)
The present study systematically reviewed the literature regarding the bond strength durability of zirconia ceramics to resin-based luting cements after application of different bonding protocols and aging conditions. Electronic searches in PubMed, Scopus, and Web of Science databases were performed for relevant literature published between January 1st 2015 and November 15th 2022. Ninety-three (93) English language in-vitro studies were included. The percentage of the mean bond strength change was recorded prior to and after artificial aging, and the weighted mean values and 95% confidence intervals were calculated. Bonding protocols were classified based on the combination of MDP/non-MDP containing cement/primer and surface pretreatment, as well as the level of artificial aging performed. Alumina sandblasting (SA) was identified as the most frequently used surface pre-treatment while an insufficient number of studies was identified for each category of alternative surface treatments. The combination of MDP cement with tribochemical silica coating (TSC) or SA yielded more durable results after aging, while the application of SA and TSC improved bond durability when a non-MDP cement and a non-MDP primer were used. TSC may lead to increased bond durability compared to SA, whereas MDP cements may act similarly when combined with SA or TSC.